The immune microenvironment in cartilage injury and repair. (1st March 2022) - Li, Muzhe; Yin, Han; Yan, Zineng; Li, Huiyun; Wu, Jiang; Wang, Yue; Wei, Fu; Tian, Guangzhao; Ning, Chao; Li, Hao; Gao, Cangjian; Fu, Liwei; et al.
Abstract: The ability of articular cartilage to repair itself is limited because it lacks blood vessels, nerves, and lymph tissue. Once damaged, it can lead to joint swelling and pain, accelerating the progression of osteoarthritis. To date, complete regeneration of hyaline cartilage exhibiting mechanical properties remains an elusive goal, despite the many available technologies. The inflammatory milieu created by cartilage damage is critical for chondrocyte death and hypertrophy, extracellular matrix breakdown, ectopic bone formation, and progression of cartilage injury to osteoarthritis. In the inflammatory microenvironment, mesenchymal stem cells (MSCs) undergo aberrant differentiation, and chondrocytes begin to convert or dedifferentiate into cells with a fibroblast phenotype, thereby resulting in fibrocartilage with poor mechanical qualities. All these factors suggest that inflammatory problems may be a major stumbling block to cartilage repair. To produce a milieu conducive to cartilage repair, multi-dimensional management of the joint inflammatory microenvironment in place and time is required. Therefore, this calls for elucidation of the immune microenvironment of cartilage repair after injury. This review provides a brief overview of: (1) the pathogenesis of cartilage injury; (2) immune cells in cartilage injury and repair; (3) effects of inflammatory cytokines on cartilage repair; (4) clinical strategies for treating cartilage defects; and (5) strategies for targeted immunoregulation in cartilage repair. Statement of Significance: Immune response is increasingly considered the key factor affecting cartilage repair. It has both negative and positive regulatory effects on the process of regeneration and repair. Proinflammatory factors are secreted in large numbers, and necrotic cartilage is removed. During the repair period, immune cells can secrete anti-inflammatory factors and chondrogenic cytokines, which can inhibit inflammation and promote cartilage repair. However, inflammatory factors persist, which accelerate the degradation of the cartilage matrix. Furthermore, in an inflammatory microenvironment, MSCs undergo abnormal differentiation, and chondrocytes begin to transform or dedifferentiate into fibroblast-like cells, forming fibrocartilage with poor mechanical properties. Consequently, cartilage regeneration requires multi-dimensional regulation of the joint inflammatory microenvironment in space and time to make it conducive to cartilage regeneration. Graphical abstract: Image, graphical abstract